Exhumation, from tomb violation to immortality strategy - fusco, roberta; Tesi, Chiara; Licata, Marta; Larentis, Omar; Ciliberti, Rosagemma; Garberi, Cesare (Medicina Historica, 2022)
The exhumation, is the procedure of opening the tomb, unearthing and recovery of the mortal remains from the sepulchre.  Despite the reluctance towards the violation of the burials in all cultures and in all historical periods, the exhumation action underlying the study of ancient necropolises and the knowledge that derives from them, took place over time and still occurs in different populations for very sundry reasons. If we exclude accidental causes and the ordinary disinterment practiced today to create space in western cemeteries, it is observed that from an anthropological and historical point of view the exhumation, going against what is an innate principle of human nature, has always been a dense choice of cultural, political, ideological, and religious meanings, charged with serious implications of social and moral order.